2023
DOI: 10.1038/s41467-023-41800-x
|View full text |Cite
|
Sign up to set email alerts
|

FGF18 alleviates hepatic ischemia-reperfusion injury via the USP16-mediated KEAP1/Nrf2 signaling pathway in male mice

Gaozan Tong,
Yiming Chen,
Xixi Chen
et al.

Abstract: Hepatic ischemia-reperfusion injury (IRI) is a common complication occurs during hepatic resection and transplantation. However, the mechanisms underlying hepatic IRI have not been fully elucidated. Here, we aim to explore the role of fibroblast growth factor 18 (FGF18) in hepatic IRI. In this work, we find that Hepatic stellate cells (HSCs) secrete FGF18 and alleviates hepatocytes injury. HSCs-specific FGF18 deletion largely aggravates hepatic IRI. Mechanistically, FGF18 treatment reduces the levels of ubiqui… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Our previous study demonstrated that FGF18 plays a protective role in the liver, especially in liver fibrosis and hepatic ischemia-reperfusion [ 28 , 29 ]. In the present study, we found that FGF18 was increased upon LPS stimulation, and FGF18 treatment could decrease the phosphorylation of IκBα, and this effect was also correlated to a parallel decrease in the nuclear translocation of the NF-κB p65 as confirmed by immunofluorescence and western blotting analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study demonstrated that FGF18 plays a protective role in the liver, especially in liver fibrosis and hepatic ischemia-reperfusion [ 28 , 29 ]. In the present study, we found that FGF18 was increased upon LPS stimulation, and FGF18 treatment could decrease the phosphorylation of IκBα, and this effect was also correlated to a parallel decrease in the nuclear translocation of the NF-κB p65 as confirmed by immunofluorescence and western blotting analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In order to determine whether the downregulation of oxidative stress induced by GSH depends on the activation of the Nrf2 pathway, we treated RIN-m5F cells with the Nrf2 inhibitor ML385, which inhibits the activity of Nrf2 by binding to Neh1, a CNC-bZIP domain that allows Nrf2 to heterodimerize with small Maf proteins, blocking Nrf2 transcriptional activity [34,35]. Our observations revealed that inhibiting Nrf2 activity abolished the GSH-mediated nuclear translocation of Nrf2 (Figure 5A,B) and suppression of ROS production (Figure 5C) induced by OsG in β-cells.…”
Section: Inhibition Of Nrf2 Abrogates the Cytoprotective Effects Of G...mentioning
confidence: 99%
“…During hepatic IR, sudden intense oxidative stress and an inflammatory response can directly lead to hepatocyte injury and necrosis 7–11 . Inflammatory cytokines and chemokines produced by damaged hepatocytes are involved in the recruitment of immune cells to the liver, causing immune activation together with activation of the complement cascade, culminating in hepatic IRI 3,12–15 . Interestingly, complement activation products also participate in the clearing of dead hepatocytes after liver IR, and promote hepatocyte proliferation and initiation of liver repair processes 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Hepatic ischemia reperfusion (IR) is a major cause of liver damage, organ rejection and sometimes hepatic failure, and is commonly happened following hepatic lobectomy and hepatic transplantation. 1 , 2 , 3 , 4 IR injury (IRI) in liver is an inevitable outcome of liver transplantation and resection surgery, so understanding the pathogenesis of liver IRI is important for optimizing surgery success. 5 , 6 During hepatic IR, sudden intense oxidative stress and an inflammatory response can directly lead to hepatocyte injury and necrosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation